Fast-Track Insolvency Refinancing Procedure (PARC): preliminary analysis regarding a possible extension - Aragón Samanez, Sol Ivanna (2020)
The arrival of the Fast-Track Insolvency Refinancing Procedure (PARC for its initials in spanish) was not fortuitous. In order to face the global health crisis, the Peruvian government not only has been taking exceptional actions related to the sanitary system, but also has been concerned about the businesses affected by the COVID-19 pandemic. Likewise, this procedure has been created as a complementary action, with the purpose of refinancing the obligations of the companies that suffered the effects of the pandemic. Furthermore, as the first entirely virtual fast- track procedure, and also because of its development in a shorter time compared to the other existing procedures in Perú, the PARC is unique.Due to these advantages, this article will try to explain why the PARC should not only be valid until December 31st, 2020. The continuity of this procedure in the post-pandemic stage is necessary, since the economic crisis will doubtlessly have long-term effects. Nonetheless, different questions arise regarding the permanence of this procedure in our legal system. Among these, the main questions are related to the similarity of the PARC with the Preventive Bankruptcy Procedure and also some administrative “flaws”. This will be analyzed throughout the text.